World robot summit 2020 assembly challenge – summary of the competition and its outcomes*. (17th November 2022) - Yokokohji, Yasuyoshi; Kawai, Yoshihiro; Shibata, Mizuho; Aiyama, Yasumichi; Kotosaka, Shinya; Uemura, Wataru; Noda, Akio; Dobashi, Hiroki; Sakaguchi, Takeshi; Maeda, Yusuke; Yokoi, Kazuhito
ABSTRACT: The World Robot Summit (WRS) is a robotic 'challenge and exposition' organized by the Japanese government to accelerate social implementation, research and development of robots working in realistic daily life, society, and industrial fields. In this paper, we introduce a robot competition of the Industrial Robotics Category of the WRS, called 'Assembly Challenge', which is organized by the WRS Industrial Robotics Competition Committee in order to promote the development of the next-generation production systems that can respond to new production demands in agile and lean manners. After the pre-competition held in Tokyo in October 2018, the main competition, the WRS 2020, was originally scheduled to be held in Aichi (partly in Fukushima) in 2020, which was also the Olympic year. However, due to the pandemic of COVID-19, the event was postponed, and the competition was actually held in Aichi in September 2021. In this paper, we introduce the contents and results of the WRS 2020 and analyze the results. We would also like to summarize the 5-year project since 2017 and discuss the outcomes of the WRS. GRAPHICAL ABSTRACT: UF0001